Optimizing Role-Playing Learning Strategies and Reinforcing Self-Control toward Anti-Corruption Knowledge - Desti Pujiati; Myrnawati Crie Handini; Moch. Asmawi (JETL (Journal of Education, Teaching and Learning), 2020)
This study aimed to find out the optimizing of role-playing learning strategies and reinforcement of self-control through anti-corruption knowledge in children. It is expected that through role-play children can direct their aspirations and control themselves as a basis for reinforcement in anti-corruption knowledge. The method used in this research is the 2x2 design of the experimental method. Children can develop anti-corruption knowledge so that they can adjust it to the applicable rules or norms, build self-control positively, build habits to become individuals with honesty values and courage values, be simple, build justice and work hard in the community life where children live.